KUFRI LIMA: A NEW HEAT TOLERANT POTATO VARIETY - Luthra, Satish Kumar (Potato Journal, 2021)
Kufri Lima is a heat tolerant table potato variety suitable for early planting in North Indian plains. It is an exotic clone CIP397065.28 (CP4054) descendant of cross CIP391180.6 âˆš CIP392820.1 developed at International Potato Center, Lima, Peru. Its plants are tall and vigorous with tolerance to mite and hopper burn. The passport data reveals that it has resistance to PYX, PVY and moderate resistance to root knot nematode. It produces attractive white-cream, ovoid tubers with shallow eyes and cream flesh, possess 19% tuber dry matter and good keeping quality. Kufri Lima has ability to produce up to 19% high tuber yield than heat tolerant variety Kufri Surya in North Indian plains in 15-20 days early planted crop.